Comparison of Offering Waste Management Regulations from the Perspective of Environmental Law in Indonesia and India - Adelia Yuliana (Indonesian Civil Law Review, 2025)
Religious practices through offerings (sesajen) in Indonesia and India reflect spiritual values, communal solidarity, and reverence for the sacred, yet simultaneously create ecological challenges when residues, such as flowers, leaves, incense, plastic containers, and holy water, are discarded without proper treatment. This paradox between religious devotion and ecological preservation highlights the need for clear regulations, detailed Standard Operating Procedures (SOPs), and effective upstream management strategies. This study employs a normative legal approach using a literature review of primary legal materials, including Law No. 18/2008, Government Regulation No. 81/2012, regional policies in Indonesia, and India’s Solid Waste Management Rules 2016. Secondary sources consist of scholarly articles, books, and policy reports, while tertiary data include official websites and online news. The research aims to compare the regulatory frameworks of the two countries, identify socio-cultural, institutional, and enforcement barriers, and propose management strategies consistent with the principles of prevention, precaution, and sustainability in environmental law. Findings reveal that Indonesia’s regulatory approach remains general and dependent on local government discretion, resulting in the absence of standardized SOPs for ritual waste. India’s framework, by contrast, is more specific, covering bulk waste generator classification, mandatory segregation at the source, restrictions on hazardous materials, artificial immersion ponds, and penalty and recovery schemes. Both countries face similar challenges, including sacred perceptions hindering segregation, weak coordination, limited infrastructure, and insufficient monitoring data. Recommendations include formulating operational SOPs at national and local levels, enhancing collaboration among authorities and religious leaders, promoting education rooted in local wisdom, expanding segregation and composting facilities, incentivizing best practices, and setting measurable 3R targets supported by monitoring and sanctions.